Stopping over-medication of people with intellectual disability, Autism or both (STOMP) in England part 1 – history and background of STOMP. Issue 1 (14th September 2018) - Branford, David; Gerrard, David; Saleem, Nigget; Shaw, Carl; Webster, Anne
Abstract : Purpose: The programme – Stopping the over-medication of people with an intellectual disability, Autism or Both (STOMP) is a three-year programme supported by NHS England. Concern about the overuse of antipsychotic drugs has been a constant theme since the 1970s. However, despite a multitude of guidelines the practice continues. The report into the events at Winterbourne View not only raised concerns about the overuse of antipsychotic drugs but of antidepressants and multiple psychotropic drug use. The purpose of this paper is twofold: Part 1 is to present the history and background to the use of psychotropic drugs in intellectual disabilities, autism or both; and Part 2 presents the progress with the STOMP programme. Design/methodology/approach: The review tracks the various concerns, guidelines and attempts to tackle the issue of over medication of people with intellectual disability autism or both. Findings: The review identifies that despite the many studies and guidelines associated with the prescribing of psychotropic drugs for people with an intellectual disability, autism or both the practice is common. Programmes that minimise the use of psychotropic drugs involve a full use of the multidisciplinary team and an availability of alternative methods of managing challenging behaviours. Originality/value: STOMP is part of an English national agenda – Transforming care. The English Government and leading organisations across the health and care system are committed to transforming care for people with intellectual disabilities, autism or both who have a mental illness or whose behaviour challenges services. This review identifies many studies, programmes and guidelines associated with psychotropic drug use for people with an intellectual disability, autism or both.